Tgfbr2 inactivation facilitates cellular plasticity and development of Pten-null prostate cancer. (12th January 2018) - Zhao, Wei; Zhu, Qingyuan; Tan, Peng; Ajibade, Adebusola; Long, Teng; Long, Wenyong; Li, Qingtian; Liu, Pinghua; Ning, Bo; Wang, Helen Y; Wang, Rong-Fu
Abstract: Mutations in tumors can create a state of increased cellular plasticity that promotes resistance to treatment. Thus, there is an urgent need to develop novel strategies for identifying key factors that regulate cellular plasticity in order to combat resistance to chemotherapy and radiation treatment. Here we report that prostate epithelial cell reprogramming could be exploited to identify key factors required for promoting prostate cancer tumorigenesis and cellular plasticity. Deletion of phosphatase and tensin homolog ( Pten ) and transforming growth factor-beta receptor type 2 ( Tgfbr2 ) may increase prostate epithelial cell reprogramming efficiency in vitro and cause rapid tumor development and early mortality in vivo . Tgfbr2 ablation abolished TGF-β signaling but increased the bone morphogenetic protein (BMP) signaling pathway through the negative regulator Tmeff1. Furthermore, increased BMP signaling promotes expression of the tumor marker genes ID1, Oct4, Nanog, and Sox2 ; ID1/STAT3/NANOG expression was inversely correlated with patient survival. Thus, our findings provide information about the molecular mechanisms by which BMP signaling pathways render stemness capacity to prostate tumor cells.